ATV Car Rental Monitoring Using Android Based GPS Tracking - Romadlon, Shofiyul Irchami; Sarosa, Moechammad; Waluyo, Waluyo (Jurnal Jaringan Telekomunikasi, 2023)
In the observations of ATV car rentals that have been carried out at Cafe Sawah, officers monitor ATV cars using a monitoring tower. This system can replace the function of using a monitoring tower to make it easier to monitor ATV cars.This research will design a tool for monitoring ATV cars that makes it easier for officers to monitor ATV cars remotely. By using an arduino atmega 2560 which is used as a microcontroller and there is a nodemcu which is used to connect to the internet network, then gps neo-6m to find out the position of the ATV car. And the android application that is used to monitor ATV cars.Based on 11 rounds of testing on the ATV car trajectory that has been determined, the results of the latitude and longitude coordinates on the ATV car monitoring application with google maps as a reference are obtained. By testing 11 rounds of ATV cars, accurate results are obtained at points 1,2,3,5,8,9,10,11 and less accurate results are obtained at points 4,6,7 by comparing the coordinates obtained in the ATV car monitoring application and the coordinates obtained on google maps. While the data from the results of signal testing using the G-NetTrack Pro application, in the test drive test using the G-NetTrack Pro application, an extraordinary result was obtained with a value of -59 which was found at the 5th point and a bad result of -94 was found at the point to 4.